Examining the Interface Between Substance Misuse and Intimate Partner Violence - Peter M. Monti; David R. Strong; Deborah L. Rhatigan; Emily F. Rothman; Zach Walsh; Yael Chatav Schonbrun; Patricia R. Recupero; Shawna M. Andersen; Meggan M. Bucossi; Christopher W. Kahler; Robert L. Stout; Susan E. Ramsey; et al. (SAGE Publishing, 2009)
There is considerable theoretical and empirical support for a link between substance misuse and perpetration and victimization of intimate partner violence. This review briefly summarizes this literature and highlights current research that addresses the interface between treatment for substance abuse and intimate partner violence. Suggestions for future research and clinical implications are provided.